2019
DOI: 10.1002/14651858.cd006715.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia for adults undergoing cardiac surgery with or without cardiopulmonary bypass

Abstract: Analysis 1.11. Comparison 1 Epidural analgesia compared with systemic analgesia, Outcome 11 Duration of tracheal intubation in hours (for studies for which means and standard deviations could be extracted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 130 publications
2
55
1
1
Order By: Relevance
“…Table 3 summarizes the main features and findings of the most relevant RCTs and meta-analyses of RCTs that investigated the role of neuraxial anesthesia in patients undergoing cardiac surgery with regard to postoperative outcomes. 175,[181][182][183][184][185][186][187][188][189][190][191] The most recent and comprehensive meta-analysis included 69 RCTs (4,860 patients overall) in which epidural analgesia was compared with either intravenous analgesia, peripheral nerve block, intrapleural analgesia, or wound infiltration in adult patients undergoing any cardiac surgery. 191 Among studies using systemic analgesia as a comparator, no differences were found between arms in up to 30day mortality (3,418 patients from 38 RCTs; risk difference [RD] 0.00, 95% CI À0.01 to 0.01) and in the incidence of postoperative stroke (2,232 patients from 18 RCTs; RD À0.00, 95% CI À0.01 to 0.01), and no or little difference was found in the risk of postoperative pneumonia (1,107 patients from 10 RCTs; RD À0.03, 95% CI À0.07 to 0.01).…”
Section: Effect On Outcomes Of Neuraxial Anesthesia/analgesia As An Amentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes the main features and findings of the most relevant RCTs and meta-analyses of RCTs that investigated the role of neuraxial anesthesia in patients undergoing cardiac surgery with regard to postoperative outcomes. 175,[181][182][183][184][185][186][187][188][189][190][191] The most recent and comprehensive meta-analysis included 69 RCTs (4,860 patients overall) in which epidural analgesia was compared with either intravenous analgesia, peripheral nerve block, intrapleural analgesia, or wound infiltration in adult patients undergoing any cardiac surgery. 191 Among studies using systemic analgesia as a comparator, no differences were found between arms in up to 30day mortality (3,418 patients from 38 RCTs; risk difference [RD] 0.00, 95% CI À0.01 to 0.01) and in the incidence of postoperative stroke (2,232 patients from 18 RCTs; RD À0.00, 95% CI À0.01 to 0.01), and no or little difference was found in the risk of postoperative pneumonia (1,107 patients from 10 RCTs; RD À0.03, 95% CI À0.07 to 0.01).…”
Section: Effect On Outcomes Of Neuraxial Anesthesia/analgesia As An Amentioning
confidence: 99%
“…175,[181][182][183][184][185][186][187][188][189][190][191] The most recent and comprehensive meta-analysis included 69 RCTs (4,860 patients overall) in which epidural analgesia was compared with either intravenous analgesia, peripheral nerve block, intrapleural analgesia, or wound infiltration in adult patients undergoing any cardiac surgery. 191 Among studies using systemic analgesia as a comparator, no differences were found between arms in up to 30day mortality (3,418 patients from 38 RCTs; risk difference [RD] 0.00, 95% CI À0.01 to 0.01) and in the incidence of postoperative stroke (2,232 patients from 18 RCTs; RD À0.00, 95% CI À0.01 to 0.01), and no or little difference was found in the risk of postoperative pneumonia (1,107 patients from 10 RCTs; RD À0.03, 95% CI À0.07 to 0.01). Conversely, epidural analgesia was found to be associated with reduced rates of PMI (2,713 patients from 26 RCTs; RD À0.01, 95% CI À0.02 to 0.00), respiratory depression (1,736 patients from 21 RCTs; RD À0.03, 95% CI À0.05 to À0.01), and atrial fibrillation or flutter (2,431 patients from 18 RCTs; RD À0.06, 95% CI À0.10 to À0.01); reduced (by about 2.4 h) times to tracheal extubation (3,353 patients from 40 RCTs; standardized mean difference À0.78, 95% CI À1.01 to À0.55); and improved pain control up to 72 hours after surgery.…”
Section: Effect On Outcomes Of Neuraxial Anesthesia/analgesia As An Amentioning
confidence: 99%
“…6 Experience with regional anesthesia for cardiac surgery is quite extensive. 7,8 In both children and adults, a significant reduction in pain scores is to be expected when regional anesthesia is added in the treatment of acute postoperative pain after cardiac surgery. 7,8 The ability of regional anesthesia to decrease the occurrence of persistent postoperative pain for patients undergoing cardiac surgery is, however, not clearly established at the moment.…”
mentioning
confidence: 99%
“…Thus, neuraxial blocks are not very popular among clinicians caring for patients undergoing cardiac surgery due to a potential increased risk in this population (3 per 10,000 v 1 per 10,000 in the general population). 7 For this reason, superficial blocks, defined as being performed at a compressible site, [9][10][11] are gaining popularity. Although not completely lacking risks of hematoma formation, the goal is to decrease the risk of permanent neurologic injury associated with a hematoma at the puncture site.…”
mentioning
confidence: 99%
See 1 more Smart Citation